Using theoretical frameworks to analyze democratic student–teacher engagement and autonomous learning for academic achievement in Zimbabwe - Magwa, Logic; Mohangi, Kamleshie (Frontiers in Education, 2022)
Positive student–teacher engagement that fosters independent and supported learning is the fulcrum for academic success. This paper investigates stakeholder opinions on the intrinsic importance of a democratic student–teacher relationship and autonomous learning in mediating students’ academic progress in Zimbabwean secondary schools. This case study’s qualitative data was gathered through interviews and focus groups. We used Foucault’s theory of power relations and the self-determination theory of motivation to frame our findings. The 40 participants from two secondary schools were general teachers (n = 12), guidance and counseling teachers (n = 2), educational psychologists (n = 2), and form 5 students (n = 24), selected through purposive sampling techniques. The data were analyzed using the thematic content analysis approach. Findings revealed participants’ perceptions that democratic student–teacher relationships and autonomous learning opportunities may serve as a panacea to enhance students’ participation, motivation, and overall academic performance. The study recommends in-service training to teachers regarding policies, directives, and public acts that inform and educate on how student–teacher relationships may be enhanced to foster autonomous learning. Future longitudinal studies could investigate the long-term effects of positive student–teacher engagement and teacher-supported autonomous learning on student academic achievement.